PENGARUH PIJAT OKETANI TERHADAP PEMBENGKAKAN PAYUDARA (BREAST ENGORGEMENT) - Marsiami, Azizati Salmas (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023, 2023)
Breast engorgement is a problem that is often found in breastfeeding mothers. A further impact breast engorgement of experienced by mothers is severe breast pain so that mothers give up breastfeeding and switch to formula milk. Oketani massage is an alternative to overcome lactation problems such as breast swelling, mastitis, and not enough milk or sore nipples. The purpose of this study was to analyze the effect of Oketani massage on breast engorgement in breastfeeding mothers in Trimulyo Health Center. This study used a quantitative method with a randomized controlled trial (RCT) post test only control group design. The subjects of this study were breastfeeding mothers on days 1-14 postpartum in Trimulyo who met the inclusion criteria and did not meet the exclusion criteria. Subjects were divided into 2 groups: 30 control groups and 30 treatment groups. The control group consisted of 30 people who were given KIE breast care, while the treatment group was breastfeeding mothers 1-14 days postpartum who were given Oketani massage. Data were collected using the Visual Analog Scale. The results of the analysis using the T-Test obtained p-value of 0,000 (? 0,05), which means that there was an effect of giving Oketani massage on reducing breast engorgement in breastfeeding mothers at the Trimulyo Health Center. In addition, the results of the analysis used the Chi-square test with a value of p = 0,000 with an RR of 10,3 (95% CI). This means that the group that was not given Oketani massage had a risk of 10,3 times breast engorgement compared to the treatment group. Oketani massage is effective for reducing breast engorgement in breastfeeding mothers.